“I want to go again and again”: Spiritual Emotions And Self-Improvement Through Pilgrimage: “I want to go again and again”: Spiritual Emotions And Self-Improvement Through Pilgrimage - Claudia Seise (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2019)
This article aims to understand what it is that has made and still makes millions of Muslims taking great physical and financial hardship to go on the Muslim pilgrimage. It seems that the reason why Muslims yearn to visit Mecca has to be understood by looking at what emotions, and especially spiritual emotions, are triggered through this visit or even through the imagination of visiting the holy land. This yearning cannot just be understood based on wanting to fulfill one of the five pillars of Islam. Religious or spiritual travel like the journey to the holy land of Islam needs to be understood within the context of an individual’s emotional landscape, spiritual development and urge for spiritual self-improvement to become a better person and Muslim. This article used qualitative method, particularly semi-structured interviews with the informants. The results showed that pilgrimage to the Muslim holy land in Mecca can be a changing experience for the pilgrim undertaking the journey.